1998
DOI: 10.1016/s0735-1097(98)00145-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Circulating Cellular Adhesion Molecules in Postmenopausal Women With Coronary Artery Disease

Abstract: A possible mechanism by which E2 exerts one of its cardioprotective effects is by limiting the inflammatory response to injury by modulating the expression of CAMs from the endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
48
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(55 citation statements)
references
References 26 publications
6
48
0
1
Order By: Relevance
“…For example, Cushman et al 13 found that estrogen only and estrogen/progestin therapy were both associated with an increase in CRP levels of Ն1 SD compared with baseline, and Caulin-Glauser et al 15 found that hormone replacement compared with no treatment was associated with a change in ICAM-1 levels of Ͼ3 SDs. Therefore, the present study was powered to detect even a relatively modest androgen-related change in inflammatory marker levels compared with effects previously observed in the sex steroid studies reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cushman et al 13 found that estrogen only and estrogen/progestin therapy were both associated with an increase in CRP levels of Ն1 SD compared with baseline, and Caulin-Glauser et al 15 found that hormone replacement compared with no treatment was associated with a change in ICAM-1 levels of Ͼ3 SDs. Therefore, the present study was powered to detect even a relatively modest androgen-related change in inflammatory marker levels compared with effects previously observed in the sex steroid studies reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In contrast, HRT reduces circulating levels of cell adhesion molecules, such as ICAM-1, VCAM-1, and E-selectin. [15][16][17][18] The effects of exogenous androgens on inflammatory markers have not been examined. We have previously shown that androgens increase endothelial VCAM-1 expression in vitro, 19 and we now report the effects of androgen treatment on serum inflammatory markers in healthy older men.…”
mentioning
confidence: 99%
“…Recent publications point to an estrogen-related limitation of inflammatory responses in peripheral tissues 11,12 due to a decreased expression of adhesion molecules, including vascular cell adhesion molecule-1, E-selectin, and intercellular adhesion molecule-1. There is not, however, a clear consensus on whether estrogen acts directly or indirectly to decrease leukocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested other potentially antiatherogenic effects of estrogen, including beneficial effects on the lipid profile, 6,7 coagulation factors, 12 cell adhesion molecule expression, 31,32 arterial plaque size, and cellular proliferation. 33 In an immortalized cell line that does not express estrogen receptors, supraphysiological doses of 17␤-estradiol have been shown to decrease lipid uptake by macrophages 25 ; however, the effects of physiological levels of estrogen and its antagonists on foam cell formation and the mechanism of lipoprotein uptake in female and male primary human macrophages have not been studied previously.…”
Section: Discussionmentioning
confidence: 99%